2013
DOI: 10.1111/j.1540-8183.2013.12018.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Balloon Size on Aortic Regurgitation in Neonates Undergoing Balloon Aortic Valvuloplasty—A Retrospective Study Over an 11‐Year Period

Abstract: This study did not show any significant relationship between the balloon to annulus ratio during interventional dilatation and the degree of aortic regurgitation following the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…We chose to exclude studies without all information as the accuracy of extracted data deteriorates. In this way we were able to recreate individual patient data and combine data from comparative studies with data from single‐arm studies of SAV and BAV …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to exclude studies without all information as the accuracy of extracted data deteriorates. In this way we were able to recreate individual patient data and combine data from comparative studies with data from single‐arm studies of SAV and BAV …”
Section: Discussionmentioning
confidence: 99%
“…When multiple studies were reported from the same institution with potentially overlapping patients, the most recent study was used. After application of the inclusion/exclusion criteria, 20 studies were eligible for the meta‐analysis (Figure ) . Two database studies were included that may have overlapping patients with other single‐center reports …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, literature on the correlation of echocardiographic and angiographic measurements of the PV is scarce. Previous studies have demonstrated a discrepancy between the echocardiographic and angiographic measurements of the aortic valve , but a good correlation for the PV . We sought to establish the relationship between the angiographic and echocardiographic PV annulus measurements, in an effort to optimize the integration of these different measurement techniques for this procedure, and to determine whether in selected cases the balloon size could be selected without radiation and contrast exposure.…”
Section: Introductionmentioning
confidence: 88%
“…One study showed that balloon size does not correlate with the degree of aortic insufficiency immediately following the procedure or at 6-week and 1-year follow-up. 8 The authors used a balloon to annulus range of 0.7-1.6; however, the average was 0.9 and no long-term follow-up was reported.…”
Section: Technical Aspectsmentioning
confidence: 99%
“…While it is not clear that larger diameter balloons cause higher grade aortic insufficiency, most operators will keep the final balloon to annulus ratio at 0.9–1.0, particularly in neonates. One study showed that balloon size does not correlate with the degree of aortic insufficiency immediately following the procedure or at 6-week and 1-year follow-up 8 . The authors used a balloon to annulus range of 0.7–1.6; however, the average was 0.9 and no long-term follow-up was reported.…”
Section: Technical Aspectsmentioning
confidence: 99%